2021
DOI: 10.1071/cp20519
|View full text |Cite
|
Sign up to set email alerts
|

Selenium application influenced selenium biofortification and physiological traits in water-deficit common bean plants

Abstract: Agronomic biofortification with selenium (Se) maybe employed to improve the nutritional value of food crops while increasing the plant’s tolerance to water deficit conditions. Although not essential for plants, Se may increase plant tolerance to water stress by boosting plants’ defence system activity. This study aimed to enrich common bean grains with Se and alleviate water deficit effects on common bean by applying Se to plants growing under greenhouse. Selenium was applied to soil at 0, 0.25, 0.5, 1.0, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…Biofortification can be performed through conventional plant breeding or modern biotechnology (genetic biofortification) or by increasing Se uptake via Se supplementation to plants (agronomic biofortification) [ 4 , 9 , 10 , 11 ]. Agronomic biofortification has been effective in increasing the content of Se in several grain crops, such as wheat [ 12 , 13 ], rice [ 14 ], common bean [ 15 , 16 ], and sorghum [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biofortification can be performed through conventional plant breeding or modern biotechnology (genetic biofortification) or by increasing Se uptake via Se supplementation to plants (agronomic biofortification) [ 4 , 9 , 10 , 11 ]. Agronomic biofortification has been effective in increasing the content of Se in several grain crops, such as wheat [ 12 , 13 ], rice [ 14 ], common bean [ 15 , 16 ], and sorghum [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although Se is not an essential element for higher plants, it has been shown to increase antioxidant activity ( Ekanayake et al, 2015 ), change carbohydrate metabolism ( Lara et al, 2019 ; Silva et al, 2020 ), protect chlorophyll, and modulate water relations ( Zhang et al, 2014 ). Se application has reduced the side effects of abiotic stress in a wide range of staple crops, such as drought in common beans and rice ( Andrade et al, 2018 ; Ravello et al, 2021 ), heavy metal exposure in wheat ( Liu et al, 2021 ; Hasanuzzaman et al, 2022 ), and salinity in maize and garlic ( Ashraf et al, 2018 ; Astaneh et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the work carried out by Deng et al (2021) , soil Se application also increased soybean yield compared with a control treatment. Previous studies have shown that Se can improve growth and increase antioxidant capacity in plants, which can affect yield, mainly when plants are exposed to stress factors ( Boldrin et al, 2013 ; Nawaz et al, 2015 ; Mateus et al, 2021 ; Ravello et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Selenium is not currently considered a plant nutrient though its beneficial effects on vegetables have been studied for over 70 years ( Lyons et al, 2009 ; Feng et al, 2013 ). Several beneficial effects of this element for plants have been reported, such as improved rice growth ( Boldrin et al, 2012 ), increased photosynthetic rate and wheat yield ( Lara et al, 2019 ), reduced production of free radicals in lettuce ( Ramos et al, 2011 ), increased protein content and total amino acids in soybean ( Zhao et al, 2019 ), and reduced the damage caused by water stress in rice and common bean plants ( Andrade et al, 2018 ; Ravello et al, 2021 ). For this reason, due to new trends in plant nutrient classification, Se and other beneficial elements (Na, Si, Al, Co, and I) may be considered plant nutrients in the future ( Brown et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%